Workplace relationships in Europe: An analysis by occupation and employment status - Barroso, M. (Intangible Capital, 2022)
Purpose: This article analyses the extent to which two objective attributes of work – employment status,and occupation – influence workplace relationships in Europe. Employing a quantitative approach, weexplore how far the segmentation of the labour market is reflected in the non-material dimensions ofworking life, seeing the nature of work and the stabilisation of employment as resources that helpexplain broader dynamics of job quality. Design/methodology: Based on three indicators of the 6th edition of the European WorkingConditions Survey – 2015 (support from colleagues; support from managers; and the quality ofrelationships), we performed two-way ANOVA to test both the primary effects of the variables‘employment status’ and ‘occupation’ on support and quality of workplace relationships, and theirinteraction effect. Additionally, we carried out a descriptive analysis of the mean scores of each of thedependent variables in the various groups of the independent variables. The survey’s sample consists of43,850 workers from 35 European countries, randomly selected by strata of the active population ineach country. Findings: The results show that workers with more stable jobs, and those who occupy positions at thetop of the ISCO-08 classification, enjoy more support and better interpersonal relationships, thussuggesting the need to extend labour market segmentation discussions to the relational spheres of work. Research limitations/implications: The statistical indicators used need a more robustoperationalisation, able to provide greater empirical validity. Other independent variables, such as theperceptions of job security or the country of work should be considered in future analysis to control forinstitutional and policy specificities. Originality/value: Research on workplace relationships tends to emphasise the effects that suchrelationships have on both organisations and individuals, usually based on case studies and individualnarratives of relationships formed in stable work contexts. In this article, we shift the focus from theeffects of workplace relationships, to the ways in which they vary in accordance with the nature of workand the objective employment conditions.